Why Desist Hyphenated Identities? Reading Syed Amanuddin's Don't Call Me Indo-Anglian - Sharma, Susheel Kumar; Шарма, Сушіл Кумар (Lesya Ukrainka Eastern European National University, 2018)
The paper analyses Syed Amanuddin’s “Don’t Call Me Indo-Anglian” from the perspective of a cultural materialist. In an effort to understand Amanuddin’s contempt for the term, the matrix of identity, language and cultural ideology has been explored. The politics of the representation of the self and the other that creates a chasm among human beings has also been discussed. The impact of the British colonialism on the language and psyche of people has been taken into account. This is best visible in the seemingly innocent introduction of English in India as medium of instruction which has subsequently brought in a new kind of sensibility and culture unknown hitherto in India. Indians experienced them in the form of snobbery, racism, highbrow and religious bigotry. P C Ray and M K Gandhi resisted the introduction of English as the medium of instruction. However, a new class of Indo-Anglians has emerged after independence which is not different from the Anglo-Indians in their attitude towards India. The question of identity has become important for an Indian irrespective of the spatial or time location of a person. У статті проаналізовано твір Седа Амануддина «Не називай мене індоанглійцем» з перспективи культурного матеріаліста. Із метою розуміння зневаги Амануддина до згаданого терміна, досліджено матрицю ідентичності, мовну та культурну ідео логію. Також обговорюється питання політики щодо уявлення себе та іншого, що призводить до утворення прірви між людьми. Береться до уваги вплив битанського колоніалізму на мову та психіку людей. Його ознаки добре простежуються в на перший погляд невинному запровадженні англійської в Індії як мови навчання, що з часом породило новий, раніше невідомий в Індії, вид чуттєвості та культури. Для індійців це втілилося у формі снобізму, расизму, інтелектуального та релігійного фанатизму. П C Рей та M K Ґанді чинили опір запровадженню англійської як мови викладання. Водночас після здобуття незалежності в Індії з’явився новий клас індо-англійців, що загалом не відрізнявся від англо-індійців у своєму ставленні до країни. Відтак, питання ідентичності постало для індійців досить серйозно, незалежно від просторових чи часових параметрів проживання особи.
Навіщо потрібно відмовитися від розщепленої ідентичності? Інтерпретація твору «Не називай мене індо-англійцем» Седа Амануддина
Keywords: hyphenated identity; hybridity; culture; English; Indo-Anglian; Syed Amanuddin; розщеплена ідентичність; гібридність; англійська мова; індо-англієць; Сед Амануддин